3(x+1,3)=7(x+1,1) -...................................................................???
Răspunsuri la întrebare
Răspuns de
3
3x + 3,9 = 7x + 7,7
3x - 7x = 7,7 - 3,9
-4x = 3,8
x = 3,8 : (- 4 )
x = ( - 0,95)
3x - 7x = 7,7 - 3,9
-4x = 3,8
x = 3,8 : (- 4 )
x = ( - 0,95)
Răspuns de
2
3(x+1,3)=7(x+1,1)
3x+3,9=7x+7,7
3x-7x=7,7-3,9
-4x=3,8
x=[tex] \frac{3,8}{-4} x=-0,95[/tex]
3x+3,9=7x+7,7
3x-7x=7,7-3,9
-4x=3,8
x=[tex] \frac{3,8}{-4} x=-0,95[/tex]
Utilizator anonim:
Cum ai pus supra ?
Alte întrebări interesante
Informatică,
8 ani în urmă
Franceza,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă